2013
DOI: 10.1371/journal.pone.0082540
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization Potential of Dental Resins: 2-Hydroxyethyl Methacrylate and Its Water-Soluble Oligomers Have Immunostimulatory Effects

Abstract: The immunostimulatory effects of the representative dental resin monomer 2-hydroxyethyl methacrylate (HEMA), a HEMA derivative that does not contain a double bond (2-hydroxyethyl isobutyrate, HEIB), and polymerized water-soluble oligomers of HEMA (PHEMA) were investigated. It is known that expression levels of either or both of CD54 and CD86 in THP-1 cells are increased by exposure to sensitizing substances. In this study, the expression levels of CD54 and CD86, the production of reactive oxygen species (ROS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…(B)]. This tendency is similar to methyl methacrylate . However, the expression profile of CD86 in THP‐1 cells treated with PEG‐DMAs was not overlapped unlike the cytotoxicity profile.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…(B)]. This tendency is similar to methyl methacrylate . However, the expression profile of CD86 in THP‐1 cells treated with PEG‐DMAs was not overlapped unlike the cytotoxicity profile.…”
Section: Discussionmentioning
confidence: 59%
“…We have previously investigated the co-stimulatory factor expression of THP-1 cells treated with HEMA and low molecular weight water-soluble PHEMAs. 11 It is revealed that the treatment of THP-1 cells with HEMA induces the cytotoxicity and the expression of co-stimulatory factors, although at a high concentration (400 lg/mL) than needed for nickel ion (50 lg/mL), a well-known sensitizing agent. This result suggests that the sensitization potential of HEMA is weak compared with nickel ion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MMA has relatively good biocompatibility, and methacrylate derivatives with several functional groups have been developed for various applications and are widely used. However, it has been shown that these polymers contain 3-5% residual monomers 1,2) that could damage tissues [3][4][5][6][7] . For development of biologically satisfactory dental materials, it is important to clarify how residual monomers affect living cells and how the monomer structures are related to their cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%